Respiratory hypersensitivity reactions to NSAIDs in Europe: the global allergy and asthma network (GA2LEN) survey. Issue 11 (11th July 2016) - Makowska, J. S.; Burney, P.; Jarvis, D.; Keil, T.; Tomassen, P.; Bislimovska, J.; Brozek, G.; Bachert, C.; Baelum, J.; Bindslev‐Jensen, C.; Bousquet, J.; Bousquet, P. J.; et al.
Abstract: Background: Nonsteroidal anti‐inflammatory drugs (NSAIDs) are among the most prevalent drugs inducing hypersensitivity reactions. The aim of this analysis was to estimate the prevalence of NSAID‐induced respiratory symptoms in population across Europe and to assess its association with upper and lower respiratory tract disorders. Methods: The GA 2 LEN survey was conducted in 22 centers in 15 European countries. Each of 19 centers selected random samples of 5000 adults aged 15–74 from their general population, and in three centers (Athens, Munich, Oslo), a younger population was sampled. Questionnaires including questions about age, gender, presence of symptoms of asthma, allergic rhinitis, chronic rhinosinusitis, smoking status, and history of NSAID‐induced hypersensitivity reactions were sent to participants by mail. Totally, 62 737 participants completed the questionnaires. Results: The mean prevalence of NSAID‐induced dyspnea was 1.9% and was highest in the three Polish centers [Katowice (4.9%), Krakow (4.8%), and Lodz (4.4%)] and lowest in Skopje, (0.9%), Amsterdam (1.1%), and Umea (1.2%). In multivariate analysis, the prevalence of respiratory reactions to NSAIDs was higher in participants with chronic rhinosinusitis symptoms (Odds Ratio 2.12; 95%CI 1.78–2.74), asthma symptoms in last 12 months (2.7; 2.18–3.35), hospitalization due to asthma (1.53; 1.22–1.99), and adults vs children (1.53; 1.24–1.89), but was not associated with allergic rhinitis. Conclusion: Our study documented significant variation between European countries in the prevalence of NSAID‐induced respiratory hypersensitivity reactions, and association with chronic airway diseases, but also with environmental factors.